Pengaruh Jumlah Penduduk, Tenaga Kerja, Pengangguran dan PDRB terhadap Pertumbuhan Ekonomi di Kabupaten Banjar - Ulpa, Syar'iah; Pahlevi, Khairi (PPJP ULM, 2021)
his research was conducted to know and describe : (1) The influences of Population, Labor, Unemployment, and GDP on Economic Growth in Banjar Regency (2) The most dominant variable affecting Economic Growth in Regency Banjar. The Data was processed by using multiple linear regression analyses with the help of SPSS software version 16. This research showed that the Population, Unemployment, and GDP variable was affecting Economic Growth in Banjar Regency. Population, Labor, Unemployment, and GDP simultaneously influence Economic Growth. In Banjar Regency, and Population Variable was the most dominant influence on Economic Growth in Banjar Regency.